Hip-Hop Music, a Coping Strategy during Covid-19 Pandemic: A Perceptual Analysis - EFURHIEVWE, Margaret Akpevweoghene; Igue, Okpeki Philo; Elijah, Kuluje Monday (dialektika kontemporer, 2024)
Music has a calming effect on the body; hence, it is relevant in coping with the anxiety of COVID-19. Against this background, this study investigated hip-hop music as a coping strategy during the coronavirus pandemic through a perceptual analysis. This study looked at how hip-hop music, when employed, was able to achieve the intended objectives of easing anxiety, stress, and apprehension during the COVID-19 era. This study utilised a phenomenological approach that identified the psychological benefits of music. Specifically, the study employed Nigerian hip-hop music produced by sixty-nine (69) respondents suffering from anxiety due to the coronavirus pandemic and the situation of the lockdown. The respondents were advised to listen to various Nigerian hip-hop songs by different artists and reflect on their emotional state. Findings revealed that music of this nature is capable of easing anxiety, stress, and apprehension when employed with close observation.